“It is to be a punishment or a pardon is granted” or Whether the Criminal Code of Ukraine needs to have incentive norms about the crimes against human freedom, honor and dignity (Law and Safety, 2018)
The paper is focused on the analysis of the stimulatory norms expediency in the criminal law of Ukraine. The objective of the paper is to reveal the significance of legal encouraging of an offender to stop his further criminal activity. Especially, it is necessary in conditions of Ukraine’s movement from a previous Soviet heritage to modern punishment standards, where criminal liability is not only punishment, but it is also a strategy to prevent a crime.According to the author’s opinion, a pardon occasionally is much more effective than a sanction, since for some cases it allows giving up a criminal act and can prevent negative consequences for an object of encroachment in such a way. Thus, there is sometimes no need to punish an offender, who is able to get a correction out of a prison. However, there should be a concrete norm to do that, inasmuch as the Criminal Code does not have sufficient extent of such norms.As it is known, a punishment is able to be effective only when an offender both got a penalty, and was pursuing his better path. By conducting a comparative analysis, the author provides scientific arguments and facts of wide range application of encouragement in the conditions of stopping a crime.There author of the paper has analyzed different viewpoints of scholars, related to the issues provided. Herewith, the author has revealed different strategies regarding the improvement of Ukrainian criminal law and practice with the incentive norms.
Keywords: incentive norms; promotion of crimes stopping; crimes against freedom; dignity and honor; trafficking in human beings; illegal deprivation; seizure of hostages